Vprašalnik za oceno funkcijskih sposobnosti otrok (PEDI) - Lenhart, Tatjana (Rehabilitacija (Ljubljana), 2010)
Background: The Pediatric Evaluation of Disability Inventory (PEDI) is one of the most commonly used assessments for children with disability from 6 months to 7.5 years of age. It can be used to give functional descriptions and ability measures for all chronically ill children. The inter-rater reliability for PEDI in Slovenia has not been evaluated yet. Methods: The aim of this study was to check the inter-rater reliability by interviewing the parents of children with disabilities, physiotherapist and special needs teachers. 36 parents of children with different disabilities from 1.8 to 6.5 years of age (average 4.4, SD 1.3) were interviewed to fill in the PEDI. The children's abilities were also evaluated by a physiotherapist and seven special needs teachers. Results: The range of functional skills scores was wide. Comparison of average scores between physiotherapist and special needs teachers showed no statistically significant differences. Comparison of physiotherapist and special needs teachers with parents showed statistically significant differences. Intraclass correlation between physiotherapist and special needs teachers was very high (mean ICC = 0.99). Intraclass correlations between physiotherapist and parents and between special needs teachers and parents were somewhat lower (ICC = 0.75- 0.97). Conclusions: Highinter-rater reliability between physiotherapist, special needs teachers and parents for PEDI in Slovenia was proved to be high. The Slovenian translation of PEDI is a reliable test for the population of all chronically ill children. PEDI can be used for more objective and exact communication between different therapists and between different institutions.
Keywords: child; diagnostika; funkcijske sposobnosti; ocenjevanje; otroci; rehabilitacija; Robotics; vocational rehabilitation; zanesljivost